STRATEGY FOR DEVELOPING CATFISH CONSUMPTION CULTIVATION BUSINESS IN ECOTOURISM AREA, PEGUYANGAN, NORTH DENPASAR - I Gusti Ngurah Sugiana; Dewa Nyoman Sadguna; I Nyoman Yoga Parawangsa; Kadek Johan Okan Adnyana; Ngurah Agus Crisna Aryan Budiarsa (CV. Radja Publika, 2024)
The purpose of this study is to determine the development strategy for catfish consumption cultivation business using SWOT analysis and SWOT matrix to determine the position of Pokdakan Mina Mandiri in which quadrant so that the development strategy for catfish consumption cultivation business used is appropriate for business sustainability. Research This uses a descriptive method with location determination by purposive sampling. considering that the research location has been raising consumption catfish for quite some time. Results analysis SWOT shows that the position of cultivators in developing the consumption catfish cultivation business is at quadrant III Turn Around/Stability (Change Strategy) Which to be continued with matrix SWOT so that the right strategy is obtained, namely the WO strategy, namely utilizing opportunities that exist by improving the internal weaknesses of Mina Mandiri group members. So the development strategy: (1) Cultivators can increase business capital by submitting proposals to local governments and BUMN (State-Owned Enterprises) and also through soft credit loans such as KUR (People Business Credit Program), (2) Cultivators can maintain stable catfish prices so that they can further encourage the spirit of the next farming business, (3) Cultivators can make alternative feed to prevent the cost of purchasing factory feed from increasing, (4) Cultivators can look for alternative markets other than the local market to maintain during simultaneous harvests so that prices do not fall or explore the online market, (5) Cultivators can take advantage of local government policies that support seeding activities so that businesses can develop more rapidly, and (6) Opportunities to meet the demand for fishing ponds must be considered because fishing ponds have quite a large potential to absorb catfish for consumption